The language shift of Bahasa Melayu Langkat among teenage speakers in Stabat, Langkat Regency, Indonesia: A sociolinguistic study - Adisaputera, Abdurahman; Hadi, Wisman; Sari, Yuliana; Yuhdi, Achmad (Research Journal in Advanced Humanities, 2025)
This research aims to explore the shifts in the local character of BML by teenage speakers in Stabat city, Langkat regency through code-mixing and code-switching phenomena. This research used qualitative approach.  The observation was done to obtain the data from several locations in Stabat city where the language is used such as homes, markets, public places, places of worship, and places where the traditional ceremonies take place.  The data collection was performed by using disguise and inducement techniques. The results prove that the lingual forms appear in the interactions of teenagers’ verbal communication with various interlocutors. It also indicates that there are code switching and code-mixing usages in different domains such as in family and neighbors.  In code mixing events, mixed forms of BML and Bahasa Indonesia (BI) appear. These mixed forms imply a loss of identity in the teenagers’ community because the shifting forms are typical BML forms which characterize the BML which is different from the BI. In cultural lingual way, the forms which are the markers of identity for BML speakers have been shifted to lingual forms which are markers of identity for BI speakers.